The people of Kazakhstan as one of the subjects of lawmaking - Zharbolova, A.; Dossayeva, A. (Journal of actual problems of jurisprudence, 2018)
The article deals with the legislative activity of the people of Kazakhstan through direct implementation or through their representatives. The Constitution of the Republic of Kazakhstan provides 3 ways of lawmaking: Parliament of Kazakhstan, the President of the Republic of Kazakhstan and the people of the Republic of Kazakhstan. The people of Kazakhstan is the central subject of legislation. All methods of legislation are carried out with the participation of the people. All methods of legislation are carried out with the participation of the people. It comes from the constitutional provisions enshrining the people of Kazakhstan as the sole source of state power. According to the Constitution of Kazakhstan people exercise power directly, as well as delegate the execution of their power to state institutions. Key words: power, people, right, subjects, legislation.